Multiple cutaneous circumscribed lymphangiomas. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2016)
We could not find in the literature cases similar to what we describe here, characterized by circumscribed lymphangiomas (customary name that we prefer even aware that these are small lymphatic microcystic malformations), randomly distributed throughout the skin and probably present since birth even if they were noted for the first time at 2 years of age due to their poor visibility. Although their distribution is reminiscent of the familial glomus tumors and cutaneous hemangiomatosis, the transitory color changes from white to bluish-red of the individual elements and the microcystic dermoscopy finding testify on behalf of their lymphatic nature. The term lymphangioma should be reserved for acquired progressive lymphangioma or benign lymphangioendothelioma (4), due to a proliferation of lymphatic endothelial cells, which is clinically manifested by a reddish plaque on the abdominal wall or lower limbs; we do not use the term diffuse lymphangiomatosis (5), although it would be justified by the distribution of the lesions similar to that of hemangiomatosis, because this term is used in the literature for severe, progressive malformations, infiltrating the chest and abdominal cavities (2). Circumscribed lymphangiomas are really lymphangiectases, whether they are acquired and secondary to tumors (1), radiotherapy (3) or otherwise obstruction of the normal lymph circulation, whether they are congenital and separated from normal lymph circulation. It should not be considered strange that congenital circumscribed lymphangiomas should undergo transient changes in color from white to bluish-red due to spontaneous or traumatic intralesional hemorrhage, because the lymphatic and venous malformations often coexist and even ultrasound can demonstrate the presence of malformed blood vessels into the interstitial tissue between the lymphatic cavities of macrocystic lymphangiomas.